2021
DOI: 10.1063/5.0066935
|View full text |Cite
|
Sign up to set email alerts
|

1D photonic crystal direct bandgap GeSn-on-insulator laser

Abstract: GeSn alloys have been regarded as a potential lasing material for a complementary metal-oxide-semiconductor-compatible light source. Despite their remarkable progress, all GeSn lasers reported to date have large device footprints and active areas, which prevent the realization of densely integrated on-chip lasers operating at low power consumption. Here, we present a 1D photonic crystal nanobeam with a very small device footprint of 7 lm 2 and a compact active area of $1.2 lm 2 on a high-quality GeSn-on-insula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 45 publications
1
33
1
Order By: Relevance
“…Emission of the cavity provide the privilege of inspecting the spectral response from an internal source, overcoming the issues of coupling to an external waveguide and the resulting irrelevant resonant modes. Ge 9 , 10 and 22 24 alloys are being investigated as candidate materials for CMOS-compatible light sources. Thus, in our study we have integrated our design on a Ge micro-gear cavity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emission of the cavity provide the privilege of inspecting the spectral response from an internal source, overcoming the issues of coupling to an external waveguide and the resulting irrelevant resonant modes. Ge 9 , 10 and 22 24 alloys are being investigated as candidate materials for CMOS-compatible light sources. Thus, in our study we have integrated our design on a Ge micro-gear cavity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, on-chip optical communications with two-dimensions of multiplexing—wave and space division multiplexing—for extremely high data-rates 31 . Consequently, Ge was chosen being a promising CMOS-compatible gain medium 9 , 10 , 25 29 , especially with the recent lasing reports of Ge and 22 24 , although the cavity concept applies to any waveguiding material. This is evident in the sharp-peak resonances observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…36 Hyo-Jun Joo et al prepared 550 nm thick, 10.6% Sn content GeSn layer deposited on Al 2 O 3 and SiO 2 insulating layers on Si, then the Al 2 O 3 layer was selectively etched so that GeSn is on SiO 2 , which serves in optical confinement and enhances the GeSn emission threshold. They obtained 2204 nm lasing line with a pumping threshold density of 18.2 kW cm −2 at 4 K. 138 Youngmin Kim et al prepared a p–i–n heterostructure of 3 GeSn layers with 5–7–5% Sn content deposited on 130 and 200 nm buffer GeSn layers on Ge above the Si substrate, then the Ge buffer was selectively etched so that 11 μm diameter microdisk was directly stacked on Si. A 2215 nm lasing line was detected at 4 K with a pumping threshold power equal to 60 kW cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this research, the first optically pumped FP cavity GeSn laser was demonstrated at low temperature [ 32 ]. From then on, other lasers were successfully demonstrated: GeSn micro-disk lasers [ 33 ], 2D hexagonal photonic crystal (PC) cavity GeSn lasers [ 34 , 35 ], micro-bridge cavity GeSn lasers [ 36 ], 1D PC cavity GeSnOI lasers [ 37 ], GeSn/SiGeSn quantum wells lasers [ 38 ], GeSn micro-disk continuous wave (CW) lasers [ 39 , 40 ] and electrically pumped GeSn/SiGeSn lasers [ 41 , 42 ]. However, their thresholds were still very high, necessitating strategies to achieve both room temperature lasing and low thresholds.…”
Section: Introductionmentioning
confidence: 99%